PENGARUH DESAIN KANTOR TERHADAP PRODUKTIVITAS KARYAWAN DI PUSKESMAS BATANG - Arija, Haifa Hannum; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2017)
This study aims to investigate the effect of office design on employeeâ€™s productivity at Community Health Centre of Batang I, II, III and IV in Batang SubDistrict. The techniques of data analysis in this research includes validity, reliability, classic assumption test, t test, F test, the coefficient of determinationÂ  and multiple linear regression analysis to determine the effect of five variables office design. Respondents in this study were 118 employees. The results indicates that there are : furniture has positive and significant impact to the employee productivity, noise has negative and not significantly impact to the employee productivity, temperature has positive and significant impact to the employee productivity, lighting has positive and not significantly impact to the employee productivity and spatial arrangements has positive and significant impact to the employee productivity. Based on the result of the F test is known that a significant impact between variable of office design and employee productivity. Office design factors have 46,3% influence on employee productivity at Community Health Centre of Batang I, II, III and IV in Batang Sub-District, while 53,7% are influenced by other factors outside the office design factors. The result of this study can help Community Health Centre of Batang management make improvements or increases to office design factors in order to better employee productivity.